Pengaruh Project Based Learning Terhadap Berpikir Kritis dan Hasil Belajar Kognitif Peserta Didik IPA Biologi - Delta Olevia; Irwandi; Mariana Ade Cahaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of the Project-Based Learning (PjBL) model on students' critical thinking skills and cognitive learning outcomes in Biology science learning at Budi Mulia Junior High School, Bengkulu City. The research method used a quasi-experimental design with a Nonequivalent Control Group Design on 30 seventh-grade students divided into a control class (15 students) and an experimental class (15 students). The research instruments were a critical thinking ability test (5 essay questions) and a cognitive learning outcome test (10 multiple-choice questions) on the classification of living things. Data were analyzed using the Mann-Whitney test with SPSS. The results showed a significant difference in critical thinking skills with a significance value of 0.002 <0.05 and cognitive learning outcomes with a significance value of 0.007 <0.05 between the control and experimental classes. The average posttest score for critical thinking (88.67) and cognitive learning outcomes (88.67) of the experimental class was higher than the control class (81.33 and 83.33). It was concluded, the PjBL model significantly improved students' critical thinking skills and cognitive learning outcomes in Biology. Keywords: Biology Science, Cognitive Learning Outcomes, Critical Thinking, Learning, Project-Based Learning